Recognizing Personality Traits Using Consumer Behavior Patterns in a Virtual Retail Store - Khatri, Jaikishan; Marín-Morales, Javier; Moghaddasi, Masoud; Guixeres, Jaime; Giglioli, Irene Alice Chicchi; Alcañiz, Mariano (Frontiers in Psychology, 2022)
Virtual reality (VR) is a useful tool to study consumer behaviour while they are immersed in a realistic scenario. Among several other factors, personality traits have been shown to have a substantial influence on purchasing behaviour. The primary objective of this study was to classify consumers based on the Big Five personality domains using their behaviour while performing different tasks in a virtual shop. The personality recognition was ascertained using behavioural measures received from VR hardware, including eye-tracking, navigation, posture and interaction. Responses from 60 participants were collected while performing free and directed search tasks in a virtual hypermarket. A set of behavioural features was processed, and the personality domains were recognized using a statistical supervised machine learning classifier algorithm via a support vector machine. The results suggest that the open-mindedness personality type can be classified using eye gaze patterns, while extraversion is related to posture and interactions. However, a combination of signals must be exhibited to detect conscientiousness and negative emotionality. The combination of all measures and tasks provides better classification accuracy for all personality domains. The study indicates that a consumer’s personality can be recognized using the behavioural sensors included in commercial VR devices during a purchase in a virtual retail store.